Pengaruh Electronic Word Of Mouth Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Skincare Azarine Di Kota Medan - Cici Winda Atila; Ahmad Amin Dalimunte; Budi Dharma (Universitas Islam Kadiri, 2023)
In the digital age, consumers increasingly rely on the internet and social platforms for media. One emerging phenomenon is electronic word of mouth . This refers to sharing information and reviews about products and services offered by individuals through online platforms. The purpose of this study was to find out how product quality and electronic word-of-mouth affect consumers' desire to buy Azarine skin care products. Using quantitative methodology The study population is women in the city of Medan. A sample of 100 respondents was taken using the Slovin formula and the purposive sampling method to select respondents who met the specified criteria. Multiple linear regression was used to analyze the data with SPSS 26. These findings show that the electronic word of mouth variable shows that there is a positive and significant influence on the purchase decisions of Azarine skin care products, and the product quality variable shows a positive and significant influence. a significant influence between product quality variables on purchase intent, so that electronic word of mouth and product quality simultaneously have a significant effect on purchase decisions of Azarine skin care products in the city of Medan. Electronic word of mouth and product quality are also important factors in consumer purchasing decisions. Consumers look for products that can meet their needs and expectations.